Classification of rhetorical repetition and its types in Persian and English rhetoric: A Comparative Approach - Meysam Ebrahimi; Mehyar Alavi Moghaddam; Mohammad Davoudi (مطالعات زبانی و بلاغی)
Rhetorical repetition is a topic in the realm of figurative speech that helps the foregrounding of meaning and music in speech. This article comparatively investigates  the classification of rhetorical repetition and its variants in  Persian and English rhetoric.  As an archival research methodologically following the American School of Comparative Literature, the main aim  is to classify the types of "rhetorical repetition” in the rhetoric of Persian and English languages. The findings of the study suggests that, in the realm of both languages, repetition as a device is similar in definition and some of its types can be considered as equal.  Furthermore, some instances of repetition give rise to poetic forms in both perspectives. However, there are their distinctive aspects to be taken into consideration. The subject has received careful and systematic attention in Persian rhetoric, whereas English rhetoric is more chaotic and disorderly. While the Persian rhetoric is influenced by the Arabic rhetoric, the traces of Aristotelian or Greek rhetoric and the existence of varieties such as the repetition of al-Sadrah in the English rhetoric can be discerned.